KORELASI ANTARA MATEMATIKA DENGAN DASAR ZAT, PANAS DAN OPTIKA PADA PROGRAM STUDI PENDIDIKAN IPA - fatimatul munawaroh (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2017)
Mathematic ability is indispensable for understanding and solving problems in Physics tasks. Based on the importance of the mathematic ability, the curriculum of Natural Science Education Program consists of mathematics courses namely Mathematics I and II. The purpose of this study is to determine the correlation of learning outcomes in Mathematics dan physics courses on the topic of Basic Substance, Heat and Optics. This study was conducted on the bachelor students of Natural Science Education Program on academic year 2015/2016 consisting of 3 classes that are class A, B and C. Students have covered the course of Mathematics I, Mathematics II and physics. Data obtained by documentation technique. The result of the analysis shows that there is a significant correlation between the learning result of Mathematics subject and the result of physics course study. The correlation index between Mathematics I and physics is 0.52; 0.34 and 0.23 for class A, B and C. While the correlation index between Mathematics II and physics are 0.27; 0.34 and 0.28 for classes A, B and C. Keywords: Correlation, Mathematic abiliy, Physics